Implementation of Building Permit Services in Spatial Planning: A Case Study of Pangkalpinang City, Bangka Belitung Islands Province - Yansyah Tridarmawan Putra; Fernandes Simangunsong; Siti Julaeha (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to evaluate the implementation of Building Permit (IMB) services in achieving orderliness in spatial planning in Pangkalpinang City. Using a qualitative descriptive method, the research examines the effectiveness of the service process based on key implementation criteria: communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of Building Permits in Pangkalpinang City remains suboptimal. Several internal inhibiting factors were identified, including weak communication among policy implementers, insufficient technical staff at DPMPTSP and NAKER, inadequate supporting facilities and infrastructure, the absence of an Electronic Licensing System (PSE), lack of transparency in permit issuance, ineffective collaboration between DPMPTSP, NAKER, and the PU and City Planning Office, as well as low employee discipline within DPMPTSP and NAKER. Additionally, external factors such as community behavior further hinder the effectiveness of implementation. Theoretically, this study underscores the importance of strengthening inter-agency collaboration, enhancing human resources, and incorporating digital licensing systems to improve service efficiency. These findings contribute to the broader discourse on public service management and provide practical insights for policymakers aiming to optimize spatial planning governance.